Penerapan Metode Drill Menggunakan Media Dinding untuk Meningkatkan Keterampilan Passing Bawah pada Peserta Ekstrakurikuler Bola Voli - Tika Rahmadanti; Ever Sovensi; Hengky Remora; Hayudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of implementing a drill method using a wall as a medium in improving underhand passing skills among volleyball extracurricular participants at SMP Negeri 29 Kaur. This study used a quantitative method with an experimental design in the form of a one-group pretest-posttest. The sample consisted of 15 male volleyball extracurricular participants selected using a purposive sampling technique. Data collection was conducted through an underhand passing skills test using the AAHPER test instrument. The results showed a significant increase in underhand passing skills, as indicated by an average pre-test score of 8.33, increasing to 14.6 in the post-test. The results of the hypothesis test using the z-test obtained Z count > Z table, thus accepting the alternative hypothesis. This proves that the drill method using a wall as a medium is effective in improving underhand passing skills in volleyball. Thus, this method can be used as a simple, effective, and easy-to-implement training alternative in extracurricular activities. Keywords: Wall Media, Drill Method, Underhand Passing